Review of binary, ternary and quaternary mixtures for induction and maintenance of opioid free anesthesia - Beatriz Tauste-Hernández; Manuel Cortiñas-Sáenz; Francisco Dámaso Fernández-Ginés; Juan Miguel Expósito-López (Elsevier, 2021)
Objective: To describe and organize the current information available on binary, ternary and/or quaternary mixtures used in opioid-free anesthesia (OFA), as well as their physicochemical stability, in order to facilitate its correct administration, optimize its use, and prevent potential effectiveness and safety issues. Method: A systematic review of the literature on OFA was conducted in PubMed/Medline, Trissel, Micromedex, Lexicomp, ww.ahfsdruginformation. com, ASHP's Extended Stability for Parenteral Drugs, and www.stabilis.org. Only articles published in English or Spanish until May 2020 and with access to full text were considered. MeSH terms used included: "drug incompatibility" AND "opioid-free anesthesia" AND "administration, intravenous" AND "dexmedetomidine" AND "lidocaine" AND "ketamine" AND "magnesium sulphate" OR "infusions, intravenous. A first search was carried out in PubMed/Medline that included OFA clinical cases. The results obtained were collected in a database. A second search was carried out on the incompatibilities of intravenous mixtures. Information was compiled on mutually-compatible/incompatible drugs, reference concentrations, stability time at room temperature (23 ± 2 °C) and under refrigeration (4 ± 2 ºC), type of administration recommended, and relevant results and conclusions. Two two-dimensional tables on the compatibility of each drug combination were created for administration as Y-site infusion or as a mixture in a single solution. Results: Seven hundred and eighty articles were identified, with the full text of 203 being accessed. A total of 4,762 cases treated with OFA protocols were chronologically collected from 32 different publications. Administration of two concomitant drugs was the most usual regimen (42.4%). The most frequently drugs were dexmedetomidine (25 studies), ketamine hydrochloride (25 studies) and lidocaine (14 studies). Compatibility/incompatibility data was collected for 11 drugs, associated to 7 pharmacological groups; compatibility with Y-site administration was found in 43 of 55 combinations (78.18%) and with integration into one single solution in 13 of 55 drug combinations (23.63%). None of the sources reviewed reported any adverse results related to potential pharmacological incompatibilities. Conclusions: Despite the availability of multiple OFA protocols, few studies analyze the compatibility between binary drug mixtures. No information exists as yet regarding compatibilities in the context of ternary and quaternary mixtures. Despite the availability of multiple OFA protocols, few studies analyze the compatibility between binary drug mixtures. No information exists as yet regarding compatibilities in the context of ternary and quaternary mixtures.